Nanoparticle-imprinted polymers for size-selective recognition of nanoparticles - Kraus-Ophir, Shlomit; Witt, Julia; Wittstock, Gunther; Mandler, Daniel (Angew Chem Int Ed EnglAngewandte Chemie (International ed. in English), 2014)
Citrate-stabilized gold nanoparticles 15 nm and 33 nm in diameter were transferred concomitantly with a monolayer of positively charged polyaniline by Langmuir-Blodgett transfer at pH 5 onto a conducting indium-doped tin oxide (ITO) support. Films consisting of one to three layers of polyaniline with thicknesses of 1-3 nm were prepared and characterized by scanning electron microscopy (SEM), atomic force microscopy (AFM), and X-ray photoelectron spectroscopy. After electro-oxidation of the Au nanoparticles in 0.1 M KCl, cavities were left behind in the film that could be analyzed by SEM. These cavities were able to recapture analyte nanoparticles from a solution of pH 10 and showed size-exclusion properties. The amount of nanoparticles taken up by the cavities was conveniently analyzed by measuring the charge associated with the electro-oxidation of these particles in 0.1 M KCl after the film had been rinsed with water. The size-exclusion properties improved with the number of Langmuir-Blodgett layers transferred.[on SciFinder (R)]
MEDLINE AN 2014304303(Journal; Article; (JOURNAL ARTICLE))
Keywords: analytical methods; Imprinting; Nanoparticles; size-selective recognition; thin films